Transformasi digital manajemen risiko: Peran fintech dalam perbankan syariah modern - Kharimah, Firdha Lailatul (Maliki Interdisciplinary Journal, 2025)
Digital transformation is a key driver in shaping modern financial systems, including in the Islamic banking sector. This article aims to analyze the role of financial technology (fintech) in strengthening the sharia-based risk management system. Using a qualitative approach and a review of recent literature, this article finds that the integration of fintech in the risk management process can improve efficiency, transparency, and compliance with sharia principles. Technologies such as big data analytics, artificial intelligence (AI), blockchain, and regulatory technology (RegTech) have provided practical solutions to manage financing risk, compliance risk, and operational risk in sharia schemes. Case studies on Bank Syariah Indonesia, Bank Islam Malaysia, and Emirates Islamic Bank show that strategic partnerships with fintech providers, regulatory strengthening, and human resource transformation are key factors for the success of this digital integration. However, challenges such as limited digital literacy, non-standardized digital sharia systems, and data security risks remain as obstacles. This article recommends the development of a national Islamic fintech-risk roadmap based on collaboration between regulators, industry, and academia as a strategic step to create a resilient, innovative, and sharia-compliant Islamic banking risk management system.